LITERATURE REVIEW: COMPARATIVE TREATMENT PATTERNS OF GERD PATIENTS IN HOSPITALS - Anggi Isnaini; Vian Saltiel Harefa; Dafni Aisyah Fariby; Najwa Adella Feriska; Falesya Jovanka Athallah; Anisa Puja Ningrum; Shabina Putri Alliya; Daniah Atikah; Wafa (Journal of Research in Pharmacy and Pharmaceutical Sciences, 2025)
Gastroesophageal Reflux Disease (GERD) is one of the upper gastrointestinal tract diseases whose prevalence continues to increase globally, including in Indonesia, with the global prevalence of 8% to 33% according to World Gastroenterology Organization. Management of GERD involves two main approaches, namely lifestyle modification and pharmacologic therapy. However, the effectiveness and response of patients to drugs vary, so the selection of treatment regimens needs to be tailored to the clinical condition, patient tolerability, and applicable guidelines. This research method uses a systematic literature review approach to examine the medication patterns of GERD towards patients within a few hospitals. Literature was searched using Google Scholar with the inclusion criteria of relevant articles published in the range of 2015-2025, resulting in one main article and five supporting articles. The results showed that the pattern of GERD treatment in hospitals is generally dominated by the use of Proton Pump Inhibitors (PPIs), either as a single therapy or in combination with antacids.